(untitled) (GEOmedia, 2020)
The recent discovery of aerial photographs of the Istrian territory and coast among the WWII USAAF imagery preserved in the Aerofototeca Nazionale archives adds important information to the already rich history of this area. The aerial view captured in August 1944, shortly before the heaviest bombing in October 1944, provides useful information for the historical reconstruction of the ancient colony of Parentium.